Minds unleashed : how principals can lead the right-brained way - Donlan, Ryan A., 1967-; Gruenert, Steve (Rowman & Littlefield, 2016)
This book, your weekly reader, will allow you to have the conversations to help faculty and staff, to help kids. More importantly, these readings invite your thinking to go to different places in your mind as you search for meaning. They are designed to cause new thinking about some familiar issues, and of course, creativity in their solutions. It is this book's intent to offer solutions for leaders at all levels to do things right, and to do what's right, or better said, to do things "right-brained."